2016
DOI: 10.1007/s00277-016-2673-3
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism following hematopoietic stem cell transplantation—a systematic review and meta-analysis

Abstract: Venous thromboembolism (VTE) is a common complication of hematopoietic stem cell transplantation (HSCT). Graft-versus-host disease (GVHD) is another complication of HSCT that may modify the risk of VTE. Our objective was to explore the incidence of VTE (deep venous thrombosis and pulmonary embolism) following HSCT and to evaluate its association with GVHD. A comprehensive search of Medline In-Process & Other Non-Indexed Citations, MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Scopus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
(36 reference statements)
4
33
0
Order By: Relevance
“…[1][2][3] Despite its common occurrence, VTE treatment in this population remains challenging due to the prolonged period of chemotherapy or conditioning-induced hypoproliferative thrombocytopenia. There is currently a lack of consensus on the right approach to anticoagulation during thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Despite its common occurrence, VTE treatment in this population remains challenging due to the prolonged period of chemotherapy or conditioning-induced hypoproliferative thrombocytopenia. There is currently a lack of consensus on the right approach to anticoagulation during thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%
“…With these limitations in mind, we designed the current study using a large cohort of autologous HCT patients to explore antithrombotic management in patients on active anticoagulation for VTE. The objectives of the current study are threefold: (1) to determine the incidence of VTE recurrence and major bleeding in patients with lymphoma and multiple myeloma who undergo autologous HCT, (2) to assess the impact of continuing vs temporarily withholding anticoagulation during the period of thrombocytopenia, and (3) to explore the effect of platelet count on the risk of bleeding in patients who continued antithrombotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…VTE, a well-described morbidity post-HCT in adults [24], is also encountered clinically in children [16,23,25]. However, epidemiologic studies in pediatric HCT recipients are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies pediatric HCT recipients, if any, were not analyzed separately. In a recent meta-analysis of 6693 HCT recipients (both adult and pediatric), Zahid et al [16] observed a 5% incidence (range, 4% to 7%) of VTE. Studies in pediatric HCT recipients have been largely isolated to single-center studies, with the largest study of 95 patients reporting a 5.4% incidence (n = 5) of VTE [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation